Evolutionary Game Analysis of the Dissemination of False Information by Multiple Parties after Major Emergencies - Bowen Li; Hua Li; Qiubai Sun; Rongjian Lv; Jianbo Zhao (Complexity)
False information is always produced after the outbreak of major emergencies. Taking this into consideration, this paper discusses the behavior of multiple parties in relation to false information dissemination after major emergencies. First, a game model is constructed, using relevant knowledge of evolutionary game theory, between three parties: regulatory institutions, opinion leaders, and ordinary Internet users. Second, the model equations are solved, and the evolutionary stability strategies of each game party under different circumstances are analyzed. Third, a numerical simulation is applied to the evolutionary trends under different strategy combinations with varying parameters. The results show that the probability of each game party making ideal decisions is positively correlated with the degree of punishment imposed by regulatory institutions on opinion leaders who release false information, the reward provided by regulatory institutions on opinion leaders who release positive information, the degree of participation and satisfaction gained by Internet users in adopting positive information, the richness of authentic content released by opinion leaders, and the psychological identification of Internet users with opinion leaders. Meanwhile, the probability of each game party making ideal decisions is negatively correlated with investigation and evidence collection costs borne by opinion leaders who release positive information, the additional income for opinion leaders who have false information adopted by Internet users, the costs of Internet users’ time and energy when they adopt information released by opinion leaders, and the costs of independently judging the accuracy of information by Internet users.